Revolutionising Education: The Muni Model as a Solution to Global Literacy and Numeracy Challenges - Thakur, Ashok (International Journal of Advanced Research in Peace, Harmony and Education, 2025)
The global education system is facing a crisis, with a significant proportion of students failing to achieve basic literacy and numeracy skills. Despite increasing investments in education, traditional pedagogical approaches have proven inadequate in addressing foundational learning gaps. The Muni Education Model presents an innovative, student-centred alternative, emphasising self-learning, peer engagement, and reduced reliance on textbooks. This research paper explores the effectiveness of the Muni Model, analysing its key features, implementation strategies, and real-world impact. The findings highlight the potential of the Muni Model in transforming global education and providing scalable solutions to literacy and numeracy challenges.